Management of parasitic weeds - Punia, S. S.; Mishra, J. S.; Prasad, T. V. Ramachandra; Madhavi, M.; Gowri, K. Vijaya (Indian Farming, 2018)
Parasitic weeds are becoming major constraints to many crops in tropical agriculture and the efficacy of available means to control them is minimal. Control strategies were largely focused on agronomic practices, the use of resistant/tolerant cultivars and the use of herbicides, although success was marginal. There is, thus, an urgent need to reevaluate the control methods in the light of recent developments in herbicide molecules, crop breeding and molecular genetics and to place these within a framework that is compatible with current agronomic practices. Emphasis should be given to understand the interaction between parasitic plants and their hosts to implement sustainable means of control. Interdisciplinary research across the disciplines is required to develop effective integrated management strategy for parasitic weeds.